The Influence of the Multisensory Learning Model in Learning the Hadith of the Qur'an on the Motor Development of Madrasah Ibtidaiyah Students - Saddang, Muhammad (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2025)
This study aims to find out the extent to which the application of the multisensory learning model in the subject of Hadith Al-Qur'an affects the development of students' motor skills at MIN 1 Majene. This study uses a quantitative method with a quasi-experimental approach to test the influence of the multisensory learning model on the motor development of Class I students of MIN 1 Majene. The research approach used was quasi-experimental the entire population of 26 students was sampled through the saturated sample technique and divided into experimental and control groups. Data analysis was performed using descriptive statistics and the Wilcoxon Test to see significant differences before and after treatment. The results of the study show that the multisensory learning model has a significant influence on improving students' gross motor development in learning the Qur'an Hadith at MIN 1 Majene. The experimental group that received the treatment showed an increase in score from 8.54 to 21.77, while the control group only increased from 8.08 to 9.31, there was an increase in scores in the experimental group due to the application of a multisensory learning model that actively integrates movement activities with Qur'anic Hadith material, so that the aspects of coordination, balance, flexibility, and motor strength of students are optimally trained, while the control group only follows regular learning without significant movement stimulation. This approach has been shown to be effective in stimulating students' coordination, balance, and motor responses through visual, auditory, and kinesthetic engagement. The Wilcoxon test confirmed the significance of the change with a p< value of 0.05, indicating that the treatment had a noticeable impact.